Physical symptoms and anxiety and depression in older patients with advanced cancer in China: a network analysis - Mo Tang; Zhongge Su; Yi He; Ying Pang; Yuhe Zhou; Yu Wang; Yongkui Lu; Yu Jiang; Xinkun Han; Lihua Song; Liping Wang; Zimeng Li; et al. (BMC Geriatrics, 2024)
Abstract Background Little is understood about the association between psychosomatic symptoms and advanced cancer among older Chinese patients. Methods This secondary analysis was part of a multicenter cross-sectional study based on an electronic patient-reported outcome platform. Patients with advanced cancer were included between August 2019 and December 2020 in China. Participants (over 60 years) completed the MD Anderson Symptom Inventory (MDASI) and Hospital Anxiety and Depression Scale (HADS) to measure symptom burden. Network analysis was also conducted to investigate the network structure, centrality indices (strength, closeness, and betweenness) and network stability. Results A total of 1022 patients with a mean age of 66 (60–88) years were included; 727 (71.1%) were males, and 295 (28.9%) were females. A total of 64.9% of older patients with advanced cancer had one or more symptoms, and up to 80% had anxiety and depression. The generated network indicated that the physical symptoms, anxiety and depression symptom communities were well connected with each other. Based on an evaluation of the centrality indices, ‘distress/feeling upset’ (MDASI 5) appears to be a structurally important node in all three networks, and ‘I lost interest in my own appearance’ (HADS-D4) had the lowest centrality indices. The network stability was relatively high (> 0.7). Conclusion The symptom burden remains high in older patients with advanced cancer in China. Psychosomatic symptoms are highly interactive and often present as comorbidities. This network can be used to provide targeted interventions to optimize symptom management in older patients with advanced cancer in China. Trial registration Chinese Clinical Trial Registry (ChiCTR1900024957), registered on 06/12/2020.